Two novel variants in SCARF2 gene underlie van den Ende‐Gupta syndrome. Issue 6 (28th February 2022) - Karaer, Derya; Karaer, Kadri
Abstract: Van den Ende–Gupta syndrome (VDEGS) (MIM#600920) is characterized by skeletal and craniofacial abnormalities that include prominent ears, downslanting palpebral fissures, blepharophimosis, hypoplastic maxilla with or without a cleft palate, a narrow and convex nasal bridge and an everted lower lip, camptodactyly and arachnodactyly. Intelligence is normal. Recent studies have reported that patients with VDEGS have pathogenic variants in the SCARF2 gene on chromosome 22q11.21. Here, we report two Turkish patients with two novel variants [c.2291_2292insC (p.Ser765LeufsTer6) and c.488G>A (p.Cys63Tyr)] in the SCARF2 gene. In silico analysis predicted that both of these novel variants were pathogenic. To the best of our knowledge, this is the first case report of this syndrome in Turkey.